2021
DOI: 10.1111/mpp.13146
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of SPCSV‐RNase3 via CRISPR‐Cas13 confers resistance against sweet potato virus disease

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 51 publications
1
16
1
Order By: Relevance
“…These are further classified into types II, V, and VI: Cas9 (type‐II) and Cas12 (type‐V) proteins are RNA‐guided, DNA‐targeting endonucleases, while type‐IV Cas13 proteins are RNA‐guided and target RNA. Cas13 variants have been deployed in Nicotiana benthamiana , sweet potato, and potato for conferring resistance to RNA viruses (Cao et al., 2021; Mahas et al., 2019; Yu et al., 2022; Zhan et al., 2019; Zhang, Zhao, et al., 2019).…”
Section: Genome‐editing Technologies For Targeted Mutagenesis Applied...mentioning
confidence: 99%
“…These are further classified into types II, V, and VI: Cas9 (type‐II) and Cas12 (type‐V) proteins are RNA‐guided, DNA‐targeting endonucleases, while type‐IV Cas13 proteins are RNA‐guided and target RNA. Cas13 variants have been deployed in Nicotiana benthamiana , sweet potato, and potato for conferring resistance to RNA viruses (Cao et al., 2021; Mahas et al., 2019; Yu et al., 2022; Zhan et al., 2019; Zhang, Zhao, et al., 2019).…”
Section: Genome‐editing Technologies For Targeted Mutagenesis Applied...mentioning
confidence: 99%
“…Interestingly, this compatible interaction between the two viruses resulted in a nearly 75% editing efficiency (Uranga et al 2021b). The Cas13 nuclease can target single stranded RNA, rather than double stranded DNA targeted by Cas9, leading to interest in applications targeting RNA viruses (Cao et al 2021;Wolter and Puchta 2018;Yu et al 2021). Additionally, deactivated Cas13 (dCas13) can be used for a variety of interesting applications, including RNA virus detection by binding fluorescently-tagged dCas13 to the RNA target (Wolter and Puchta 2018).…”
Section: Available Virus-mediated Crispr/cas9 Plant Genome Editing Toolsmentioning
confidence: 99%
“…Mahas et al [ 30 ] have demonstrated that CasRx/Cas13d mediates high interference compared to Cas13a and Cas13b simultaneously against one or two different RNA viruses. A recent study on Sweet Potato Virus Disease (SPVD) resistance using the CRISPR/Cas13 system demonstrated that LwaCas13a and RfxCas13d exhibited efficient targeting activity against multiple RNA viruses simultaneously [ 44 ].…”
Section: Applications Of Crispr/cas13 Systems In Plantsmentioning
confidence: 99%